2002
DOI: 10.1159/000048671
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intracerebroventricularly and Intraperitoneally Administered Growth Hormone on Body Weight and Food Intake in fa/fa Zucker Rats

Abstract: Growth hormone (GH) possesses multiple metabolic effects, in particular with regard to glucose and lipid homeostasis. Studies on the effects of GH on body weight and food and water intake are scarce and have yielded controversial results. We investigated the effects of different modes of GH administration on the parameters of body weight and food intake as well as on insulin and leptin concentrations in fa/fa Zucker rats. In control experiments, aqua pro injectione was given. GH was administered over a time pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…We observed that the RER increased in the early afternoon in the bGH mice but several hours later in the littermate controls. This finding indicates that the transgenic mice eat more during the light phase, which is in line with the finding of another study (16) showing that GH treatment of Zucker rats made them eat more during the day period without changing the total food intake. Thus, it can be concluded that the effect of GH on food intake is dependent on the content of dietary fat and that GH probably influences the diurnal rhythm of food intake.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that the RER increased in the early afternoon in the bGH mice but several hours later in the littermate controls. This finding indicates that the transgenic mice eat more during the light phase, which is in line with the finding of another study (16) showing that GH treatment of Zucker rats made them eat more during the day period without changing the total food intake. Thus, it can be concluded that the effect of GH on food intake is dependent on the content of dietary fat and that GH probably influences the diurnal rhythm of food intake.…”
Section: Figsupporting
confidence: 91%
“…GH has been shown to increase food intake in children (12) and in experimental animals (13) but not in all studies (14 -16) including bGH transgenic mice given ordinary low-fat chow (5). It has also been shown that eating behavior changes after GH administration (16). However, no studies have been per-formed to investigate the effect of GH on intake of low-vs. high-fat diet (HFD).…”
mentioning
confidence: 99%
“…GH has also been shown to increase food intake in experimental animals in some (5) but not all studies (13)(14)(15)(16). In addition, GH administration has been shown to change eating behavior (16).…”
mentioning
confidence: 99%
“…Previous studies in humans and rodents have demonstrated that somatotropin concentrations can be correlated with increased (Iglesias et al, 2002 ), decreased (Eden-Engstrom et al, 2003;Malmlof and Johansen, 2003), or normal (Boni-Schnetzler et al, 1999;Bolanowski et al, 2002;Schulz et al, 2002) serum leptin concentrations. The serum leptin response to pST may depend on the status of carcass adipose mass, serum insulin, serum glucocorticoid, renal state, pre-experimental ST concentration, timing of collection, or other factors.…”
Section: Discussionmentioning
confidence: 97%